Collective Action in Outport Newfoundland: A Case Study from the 1830s - Little, Linda (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1990)
Abstract As a permanent population established itself on the island of Newfoundland inthe 19th century, the various sectors of society jostled each other for a share of control over their society. In the Conception Bay outports of Harbour Grace and Carbonear the social divisions and alliances which spawned an active culture of resistance formed around ethno-religious groups, political affiliation, and social class. The first part of this paper will recount a number of diverse collective plebeian acts and look at the natives and loyalties connected with each. Part two deals with election violence with which the population used informal means to affect change in a formal theatre. Section three is devoted to the largest plebeian disturbance of the decade; the 1832 sealers' strike. Here fishermen overcame their various social biases to work in class ways for their common good